Analisis Kelayakan Usaha Penyosohan Padi Menggunakan Mesin Pengering Berbahan Bakar Sekam di UD Sari Uma Bali - WIGUNA, I MADE ANANDA; SUSRUSA, KETUT BUDI; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Paddy is a crop that produce rice and it is staple for most of Indoensian. Drying is important  post-harvest handling for  paddy. Husk can be done into two ways that are mhacinery drying and sun drying. This study aims to find out how is business technique of process of hulling rice by using unshusked rice dryer with fuel of husk and how is feasibility viewed from other investment criteria. This study was conducted at UD Sari Uma Bali that it is a company have business on rice mill used machinery husk fuel dryer. The result showed that  process of hulling rice by using husk fuel dryer is technically feasible and it is able to be operated during rainy day. Financially this business is feasible conducted with result of Payback period 4,23 year, Net Preset Value  have positive value of Rp 1.360.930.972,00 bigger than zero, and Internal rate of Return (IRR) bigger than real rate of interest at market 30,03% per year, Benefit Cost Ratio of 2,32 (bigger than one). Thus business of process of hulling rice by using husk fuel dryer  by UD Sari Uma Bali is feasible. From the result of sensitivity analysis has been conducted show that usage of paddy drying machine have fuel of husk is benefit business and reliable and have fulfilff criteria of investment though experience increasing of production cost.. Keywords:    Rice huller, husk fuel dryer, financial analysis